Pendidikan Karakter Dalam Meningkatkan Kualitas Belajar Era Generasi Milenianl - As'ari, Jamaludin; Sa’adah, Nurus (Institut Agama Islam Sumatera Barat, 2023)
Abstract Etymologically, when traced from the origin of the word, the word character comes from the Latin